The Level of Emotional Fatigue of Caregivers of Dementia Patients at Dr. Soetomo Hospital Surabaya as One of the Dimensions of Caregivers Burnout - Andini Dyah Sitawati; Najwa Awwaliyah (International Journal Labs, 2025)
Dementia is a chronic, progressive and irreversible neurobehavioral syndrome disorder, but it is not included in the normal aging process. Dementia affects the patient's independence, so it requires the help of caregivers in daily activities. The burden of care that lasts for a long period of time is prone to causing emotional exhaustion, one of the dimensions of caregiver burnout. This study is a descriptive observational study that uses the Maslach Burnout Inventory-Human Services Survey (MBI-HSS) questionnaire to determine the level of emotional fatigue of caregivers of dementia patients at the Geriatric Polytechnic of Dr. Soetomo Hospital Surabaya during October 2024. This study uses consecutive sampling techniques. Of the 24 study subjects, 13 caregivers (54.2%) experienced low levels of emotional fatigue, 8 people (33.3%) experienced moderate levels of emotional fatigue and 3 people (12.5%) with high levels of emotional fatigue. Based on the results of this study, the emotional fatigue of caregivers of dementia patients at the Geriatric Polyclinic of Dr. Soetomo Surabaya Hospital during October 2024 is at a low level, which predicts a low level of caregiver burnout.